2016
DOI: 10.1021/acs.iecr.6b00532
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Retardant and Smoke-Suppressed Silicone Foams with Chitosan-Based Nanocoatings

Abstract: Flexible silicone foams (SiFs) are high-performance but flammable materials that emit dense smoke in a fire. Two type of low-cost, eco-friendly nanocoatings, i.e., chitosan (CH)/ammonium polyphosphate (APP) and CH/montmorillonite (MMT), were fabricated on SiFs through a layer-by-layer (LbL) assembly. With seven bilayers (BL) of CH/APP coatings, the limiting oxygen index (LOI) increases from 20.2% to 23.8%, the peak heat release rate (pHRR) decreases by 27.6%, and the total smoke production (TSP) decreases 42%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…To improve the flame retardancy and smoke suppression of SiFs, relevant investigations were employed. Deng et al fabricated SiFs with seven bilayers of chitosan/ammonium polyphosphate coatings; the limiting oxygen index (LOI) increased from 20.2 to 23.8 vol%, the peak heat release rate (HRR) (PHRR) decreased by 27.6%, and the total smoke production (TSP) decreased by 42%. Chruściel and Leśniak prepared flame‐retarded SiFs with 15‐wt% melamine and 15‐wt% expanded graphite, which achieved an LOI of 41 to 43 vol%.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the flame retardancy and smoke suppression of SiFs, relevant investigations were employed. Deng et al fabricated SiFs with seven bilayers of chitosan/ammonium polyphosphate coatings; the limiting oxygen index (LOI) increased from 20.2 to 23.8 vol%, the peak heat release rate (HRR) (PHRR) decreased by 27.6%, and the total smoke production (TSP) decreased by 42%. Chruściel and Leśniak prepared flame‐retarded SiFs with 15‐wt% melamine and 15‐wt% expanded graphite, which achieved an LOI of 41 to 43 vol%.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, flame‐retardant coatings are an effective and convenient method for introducing concentrated flame‐retardant materials onto the surface of FPUFs without altering its mechanical properties . More recently, layer‐by‐layer (LbL) assembly has been used to fabricate flame‐retardant coatings on various substrates; this is a versatile and cost‐effective method involving the alternate deposition of selected chemical species on substrate surfaces under driving forces such as electrostatic attraction, hydrogen bonding, and covalent bonding . For LbL‐assembled flame‐retardant coatings, previous studies have shown that the choice of flame‐retardant materials is key in designing highly effective flame‐retardant coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, because of the abundant hydrocarbon groups on its side chain, SR is a combustible material; it can combust and release choking smoke once ignited. 8 When white carbon black was added during the foaming process, the SiFs could self-extinguish without any toxic gas release. Therefore, the flame retardation properties of SiFs warrant study.…”
Section: Introductionmentioning
confidence: 99%
“…7 Deng et al fabricated flame-retardant and smoke-suppressing SiFs with seven bilayers of chitosan/ammonium polyphosphate coatings; the LOI increased from 20.2 to 23.8%, the peak heat release rate (PHRR) decreased by 27.6%, and the total smoke production (TSP) decreased by 42%. 8 When white carbon black was added during the foaming process, the SiFs could self-extinguish without any toxic gas release. 9,10 In addition, inorganic fillers (e.g., asbestos, kaolin, and carbon nanotubes) and artificial fibers are widely used in flameretardant SiFs.…”
Section: Introductionmentioning
confidence: 99%